(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To identify factors associated with the duration of urethral catheterization following benign prostatic hyperplasia (BPH) using bipolar transurethral enucleation at 108 Military Central Hospital from 2024 to 2025. Methods: A prospective, longitudinal descriptive study was conducted on a case series of 68 patients with BPH who underwent bipolar transurethral enucleation. Results: The mean duration of catheterization was 2.3±1.4 days, with a median of 2 days (IQR 2-2). Analysis showed that factors significantly associated with the duration of catheterization included post-removal complications (p<0.001), intraoperative complications (p=0.005), and trilobar prostate morphology (p=0.027). Complications during postoperative catheterization occurred in 2 cases (2.9%), while complications after catheter removal occurred in 16.2% of patients. The analysis revealed that preoperative prostate volume and the duration of catheterization itself were associated with complications after catheter removal (p<0.05). Conclusion: The duration of urethral catheterization was longer in patients with post-removal complications, intraoperative complications, and those with a trilobar prostate morphology. Factors that increased the risk of complications after catheter removal included preoperative prostate volume and a longer duration of catheterization.